Bioprospecção de metabólitos secundários da própolis marrom com potencial antibacteriano e antibiofilme frente ao microrganismo Streptococcus mutans - Andrade, Rosana Moura (2022)
Propolis is a natural product produced by bees to prevent the decomposition and development of pathogenic microorganisms in the hive. Humans use propolis to treat diseases such as microbial infections, especially of the upper respiratory tract. Among the microorganisms that cause these infections is Streptococcus mutans. The biofilm produced by this microorganism is an important virulence factor, as it protects it from the action of drugs and antiseptics. In this sense, natural antibacterial products that inhibit biofilm formation can be used as an alternative to treat infectious diseases. It was proposed, in this work, to carry out bioprospecting of secondary metabolites of brown propolis with antibacterial and antibiofilm potential against S. mutans. The crude extract (EB) of brown propolis was obtained by maceration and ultrasound. Then, the EB was fractionated by liquid-liquid partition (PLL) using hexane (Hex), dichloromethane (DCM) and ethyl acetate (AcOEt). Total phenolic compounds (CFT) and total flavonoids (TF) were quantified spectrophotometrically. The determination of antimicrobial activity was performed in 96-well plates using the microdilution method and biofilm formation was evidenced by crystal violet staining. The fraction with the greatest inhibition of growth and biofilm formation of S. mutans was submitted to classical liquid chromatography (LCC) and, later, the most active subfractions were analyzed by High-Performance Liquid Chromatography with photodiode array detector (HPLC- DAD). The identification of substances was performed by Nuclear Magnetic Resonance (NMR). Obtaining the EB presented a yield of 47.72% (± 0.41). The ethyl acetate fraction (FAE) presented the highest concentration of CFT (87.7 ± 4.93 mg/g), while the dichloromethane fraction presented the highest concentration of TF (55.3 ± 7.52 mg/g). The crude extract exhibited a minimum inhibitory concentration (MIC) of 512 µg/mL against S. mutans. DF was the most active against S. mutans, with MIC of 256 µg/mL and minimum bactericidal concentration (MBC) of 512 µg/mL, while FH had a MIC of 512 µg/mL. For inhibition of biofilm formation, FH exhibited activity at concentrations of 64, 32 and 16 µg/mL. FD, on the other hand, showed inhibition at concentrations of 32 and 16 µg/mL. In this way, the FD was subjected to the fractionation of substances by CLC giving rise to 9 subfractions. Of these fractions, SBFG and SBFH were the most active against S. mutans (MIC and CBM=128 µg/mL). After HPLC-DAD analysis, it was observed that SBFG and SBFH presented similar chemical profiles and that the UV-Vis spectra indicated the presence of flavonoids. The analysis by 1H NMR evidenced the presence of flavonoids of the flavone type. With bioprospecting, it was possible to obtain two fractions rich in flavonoids with antibacterial activity against S. mutans. Other chemical analyzes still need to be performed to elucidate the chemical structure of these flavonoids.